The Effect of Financial Literacy, Risk Tolerance on Stock Investment Decisions through Financial Behavior as a Mediating Variable - Hafitri, Nisa Elya; Norisanti, Nor; Saori, Sopyan (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of financial literacy and risk tolerance on stock investment decisions, with financial behavior as a mediating variable, on young investors who are members of the stock community on the Twitter application. Using a quantitative approach and causality associative design, this study involved 210 respondents selected through purposive sampling. Data were collected through a Likert scale-based online questionnaire and analyzed using a Structural Equation Modeling (SEM) model based on Partial Least Squares (PLS) through SmartPLS 4 software. The results showed that financial literacy has a significant positive effect on investment decisions, meaning that the higher the financial literacy, the better the investment decision. In addition, risk tolerance also has a significant positive effect, indicating that high risk tolerance encourages bolder investment decisions. Financial behavior is found to have a significant influence on investment decisions, indicating the importance of good financial behavior in improving the quality of investment decisions. Financial behavior is also proven to significantly mediate the relationship between financial literacy and risk tolerance on investment decisions, strengthening the influence of both variables. This study confirms the importance of financial literacy and positive financial behavior for young investors to improve risk analysis skills, avoid illegal investments, and maximize investment profit opportunities. The findings are expected to serve as a reference for the development of financial education and the formation of healthy financial habits among the younger generation.